CBM foam drilling fluid based on hydrophilic silica nanoparticles. (2nd November 2022) - Li, Zhiyong; Zhou, Yu; Qu, Long; Li, Huaike; Huang, Tilong
Abstract: The application of foam drilling fluid in CBM drilling is constrained by the deterioration of foam stability in complex formation conditions. This article proposed introducing nanoparticles with different wettability into system. The results showed that hydrophilic silica nanoparticles can effectively improve foam quality of the amphoteric foaming agent BS-12. It was due to that hydrophilic silica nanoparticles could block both the direction of gas diffusion and gravity drainage path to the foam liquid membrane surface. Interestingly, particle size distribution of foams also changed from "single-peaked" to "double-peaked, " which contributed to the sealing effect of foams on the microfractures in the formation. Moreover, the response surface method was adopted to optimize the dosing of drilling fluid additives and to analyze the interaction of additive dosing on the comprehensive index Fq of foams. The result of the evaluation experiments suggested that it can reduce the linear expansion rate of upper strata shale by 65% and increase the recovery rate of coal rock core by 53%. In addition, the gas permeability recovery rate of the coal core was above 90%. These findings are dedicated to promoting the application of foam drilling fluid in CBM drilling.